RETRACTED: A border surveillance system to sense terrorist outbreaks. (September 2021) - Vadivelan, N.; Taware, Shrikant; Ravi Chakravarthi, R.; Anna Palagan, C.; Gupta, Sanjai
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of the Editor-in-Chief. The authors have plagiarized part of a paper that had already appeared in IEEE Trans in Sustainable Computing, Volume 6, Issue 1, 2019, page 54-65. An Efficient WSN Based Solution for Border Surveillance. DOI 10.1109/TSUSC.2019.2904855. One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Reuse of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.